Simulation of the influence of the interface roughness on the residual stresses induced in (ZrO2+Y2O3)+NiAl-type composite coatings deposited on Inconel 713C. (February 2017) - Bolek, T.; Sitek, R.; Sienkiewicz, J.; Dobosz, R.; Mizera, J.; Kobayashi, A.; Kurzydlowski, K.J.
Abstract: Constant demand for more efficient turbine engines requires applying thermal barrier coatings (TBC) on the crucial engine components. However, one of the main problems encountered in designing new kinds of ceramic coatings intended for high temperature residential components is the residual stresses generated during the exploitation of these components at elevated temperatures. In the present work, thermal barriers (TBC) composed of ZrO2 +20%Y2 O3 and β-NiAl intermetallic diffusion layers were fabricated on Inconel 713C. The TBCs thus produced were characterized by scanning electron microscopy (SEM). The residual stresses induced in the TBC and TGO (thermally grown oxide) layers during the manufacturing process were analyzed by numerical simulations. The numerical models also permitted analyzing the influence of various interface undulation degrees including the real interface shape (which is reproduced and then introduced into the model). The results obtained showed that the level of residual stress strongly depends on the differences in the properties of the constituent materials and on the undulation ratios of the TBC layers. The numerical simulation of the real shape of the interface between the layers revealed that stress concentration zones occur not only at the peaks and valleys of the interface but also on the semi-flat surface in the midway between them.